Pelatihan dan Pendampingan Cara Cepat Mengerjakan Soal dengan Metode ESKIM Siswa SD Bimbel Paramadina Tuban - Suyanto, Ahmad; Ulya, Vita Fitriatul; Anisah, Zulfatun (PT. Cahya Edupreneur Indonesia, 2024)
This Community Service Program focuses on training and mentoring elementary school students in quickly solving exam problems using the ESKIM method at the Paramadina Tutoring Center in Tuban. The ESKIM method, which includes emotion control, time management, solving easier problems first, recalling material, and carefully reading and directly solving problems, was applied to enhance the students' academic abilities. The community service initiative utilized a ServiceLearning approach, where students, teachers, and mentors collaborated in a continuous and mutually beneficial learning process. Before the training, the 10 participating students struggled with problem-solving, with an average score of 75. After the training and mentoring, there was a significant improvement, with the students' average scores rising to 95 to 100. These results demonstrate that the ESKIM method is effective in enhancing students' abilities, and the ServiceLearning approach provides a valuable model for community service in education, facilitating the transfer of practical and relevant knowledge.